Advances in GIScience Proceedings of the 12th AGILE Conference - Sester, Monika.; Bernard, Lars.; Paelke, Volker. (Lecture Notes in Geoinformation and Cartography,, 2009)
This book combines fully peer-reviewed papers covering topical research in GIScience. Included are papers on fundamental GIScience issues (e.g. interoperability, ontology, data interpretation and data generalization), emerging new topics like the handling and analysis of moving objects, as well as state-of-the-art applications. Furthermore aspects of remote sensing and image understanding are addressed. The compilation of research papers addresses researchers, practitioners, and students interested in current findings in GIScience.